Importing Equality? The Impact of Globalization on Gender Discrimination - Sandra E. Black; Elizabeth Brainerd (Institute for the Study of Labor (IZA), 2002)
While researchers have long held that discrimination cannot endure in an increasingly competitive environment, there has been little work testing this dynamic process. This paper tests the hypothesis (based on Becker 1957) that increased competition resulting from globalization in the 1980s forced employers to reduce costly discrimination against women. The empirical strategy exploits differences in market structure across industries to identify the impact of trade on the gender wage gap: because concentrated industries face little competitive pressure to reduce discrimination, an increase in competition from increased trade should lead to a reduction in the gender wage gap. We compare the change in the residual gender wage gap between 1976 and 1993 in concentrated versus competitive manufacturing industries, using the latter as a control for changes in the gender wage gap that are unrelated to competitive pressures. We find that increased competition through trade did contribute to the relative improvement in female wages in concentrated relative to competitive industries, suggesting that, at least in this sense, trade may benefit women by reducing firms? ability to discriminate.
Keywords: J70; J31; 330; gender wage gap; discrimination; Lohndifferenzierung; Geschlecht; Globalisierung; Frauenarbeitslohn; Vereinigte Staaten